(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This research program participants by scientific concepts work exit learns sports scientific principles through context as apply through to learn special has been creative diversity research to do can Sports car through students not only of sports main principles they learn and science with sports engage in to mechanics included , but they scientific They are also learning the principles , learning for psycho-social- creative-emotional contact in the environment there is .